activation of complements pathways in patients with bachcet’s disease - AL-Joofy, Ikbal Kh.; Al- Mousawy, khalida; Muslih, raad K.; Al-Khafaji, jassim; AL-Waiz, makram M. (Journal of the Faculty of Medicine Baghdad, 2006)
Background: